Perancangan Sistem Informasi Data Stock Controlling dengan Metode EOQ - Riskian Tahmid; Fajrul Islami; Mutiana Pratiwi; Ulya Ilhami Arsyah (Universitas Putra Indonesia YPTK Padang, 2019)
Information thecnology development is quickly even in outlying places that are never feeld its benefit before, but nowdays they can deeply enjoy able with information thecnology serves in an online manner. The business are established and progressed usually organized their supply management there (in the business). Previously PT. MUTIA MULIA PADANG has difficulty in the supply of the management be cause of manual character.Controlling inventory or inventory management right is not easy. But if too little inventory results in the risk of inventory shortage, as they often can not be imported goods inventory stating sudden cessation of the production process, delays in profits, even loss of customers.It would require an inventory application to manage inventory control, then the company's needs will bemet with swift and precise, so as to control inventory. With the report in the form of file storage can allow minimize the potentially fatal errors, such as losing records. This application is built using the programming language PHP and MySQL, which assisted with modeling UML (Unified Modeling Language)